Penerapan Fungsi-Fungsi Manajemen dalam Bimbingan dan Konseling Agama Islam - Ilham Ilham (UIN Antasari Banjarmasin, 2017)
Management, both as art and as a science in the beginning to grow and thrive in business circles. In a further development of management was very necessary and beneficial to any business in various fields of life, especially in modern times it may be said that no business can be successful without implementing management. Islamic guidance and counseling as one of the efforts to improve the quality of community certainly can not run effectively and efficiently, if not by utilizing management. Therefore, if the Islamic guidance and counseling is as part of the dakwah activity in the midst of human life to be successful, then the implementation can not only rely on an individual basis but should be done through cooperation within the organization by following the principles of good management.